Sub-optimal Specificity of Modified Ziehl-Neelsen Staining for Quick Identification of Tuberculous Meningitis - Wang, Ting; Feng, Guo-Dong; Pang, Yu; Yang, Yi-Ning; Dai, Wen; Zhang, Lin; Zhou, Lin-Fu; Yang, Jia-Lei; Zhan, Li-Ping; Marais, Ben J.; Zhao, Yan-Lin; Zhao, Gang (Frontiers in Microbiology, 2016)
Background Microbiological confirmation of tuberculous meningitis (TBM) remains problematic. We assessed the diagnostic performance of a modified Ziehl-Neelsen (MZN) staining method that showed promise in earlier studies. Methods Patients evaluated for TBM in Shaanxi province, China, were prospectively enrolled from May, 2011 to April, 2013. Cerebrospinal fluid (CSF) specimens were evaluated using the Xpert MTB/RIF® assay, MZN staining, and standard biochemical and microbiological tests, together with detailed clinical and radiological assessment. Results Among 316 patients included in the study, 38 had definite TBM, 66 probable TBM, 163 possible TBM and 49 “no TBM”, using consensus uniform research case definition criteria. Comparing “definite or probable TBM” to “no TBM” MZN staining had higher sensitivity than Xpert MTB/RIF® (88.5% versus 36.5%), but greatly reduced specificity (71.4% versus 100.0%); 14/49 (28.6%) cases with “no TBM” tested positive on MZN. M. tuberculosis culture was performed in 104/179 (58.1%) of MZN positive samples; 12.5% (13/104) were positive. Using Xpert MTB/RIF® as the reference standard, MZN had a sensitivity of 92.1% (95% CI 79.2-97.3) and specificity of 71.4% (95% CI 57.6-82.2). Conclusion Xpert MTB/RIF® offered a rapid and specific TBM diagnosis, but sensitivity was poor. MZN was mainly hampered by false positives. Strategies to enhance the sensitivity of Xpert MTB/RIF® or improve the diagnostic accuracy of MZN should be explored